TWO PHILOLOGICAL NOTES - White, Heather (Myrtia, 2004)
Because of editorial interference beyond my control, two sentences not written by me crept into the printed text of my reviews published in Sic. Gymn. 2001, p. 527ff. On p. 528, the interpolated sentence beginning with "Nevertheless" and ending "actual in Homer" must be disregarded, insofar as it is mistaken. The previous sentence, written by me, makes it clear that Matthews has unreservedly accepted Giangrande’ s demonstration to the effect that the ancients, including Antimachus, believed Doric forms to be well attested in Homer: what modern glottologists1 think is of course irrelevant to the issue dealt with by me.